Micronutrients Level In Control And Malnourished Children - Dr Anju Jha**, Dr. Ravinder K. Arora*, (International Journal of Scientific Research and Management (IJSRM), 2017)
Vitamins are called micronutrients as they are needed in miniscule amount. As tiny as the amounts are,the consequences of their absence are severe. The current study was done to assess the levels of vitamins(A and E) in children suffering from P.E.M. and compared with apparently healthy children. There was asignificant decrease in the levels of vitamins in P.E.M. children as compared to control (p